Intestinal barrier dysfunction in cirrhosis: Current concepts in pathophysiology and clinical implications - Tsiaoussis, Georgios I (World J Hepatol, 2015)
The intestinal lumen is a host place for a wide range of microbiota and sets a unique interplay between local immune system, inflammatory cells and intestinal epithelium, forming a physical barrier against microbial invaders and toxins. Bacterial translocation is the migration of viable or nonviable microorganisms or their pathogen-associated molecular patterns, such as lipopolysaccharide, from the gut lumen to the mesenteric lymph nodes, systemic circulation and other normally sterile extraintestinal sites. A series of studies have shown that translocation of bacteria and their products across the intestinal barrier is a commonplace in patients with liver disease. The deterioration of intestinal barrier integrity and the consulting increased intestinal permeability in cirrhotic patients play a pivotal pathophysiological role in the development of severe complications as high rate of infections, spontaneous bacterial peritonitis, hepatic encephalopathy, hepatorenal syndrome, variceal bleeding, progression of liver injury and hepatocellular carcinoma. Nevertheless, the exact cellular and molecular mechanisms implicated in the phenomenon of microbial translocation in liver cirrhosis have not been fully elucidated yet.